Pre-Assembled Fluorescent Multivalent Probes for Imaging of Anionic Membranes - Roland, Felicia M. (Bioconjug Chem, 2017)
A new self-assembly process known as Synthavidin (Synthetic Avidin) technology was used to prepare targeted probes for near-infrared fluorescence imaging of anionic membranes and cell surfaces, a hallmark of many different types of disease. The probes were pre-assembled by threading a tetralactam macrocycle with six appended zinc-dipicolylamine (ZnDPA) targeting units onto a linear scaffold with one or two squaraine docking stations to produce hexavalent or dodecavalent fluorescent probes. A series of liposome titration experiments showed that multivalency promoted stronger membrane binding by the dodecavalent probe. In addition, the dodecavalent probe exhibited turn-on fluorescence due to probe unfolding during fluorescence microscopy at the membrane surface. But the dodecavalent probe also had a higher tendency to self-aggregate after membrane binding leading to probe self-quenching under certain conditions. This self-quenching effect was apparent during fluorescence microscopy experiments that recorded low fluorescence intensity from anionic dead and dying mammalian cells that were saturated with the dodecavalent probe. Conversely, probe self-quenching was not a factor with anionic microbial surfaces where there was intense fluorescence staining by the dodecavalent probe. A successful set of rat tumor imaging experiments confirmed that the pre-assembled probes have sufficient mechanical stability for effective in vivo imaging. The results demonstrate the feasibility of this general class of pre-assembled fluorescent probes for multivalent targeting, but fluorescence imaging performance depends on the specific physical attributes of the biomarker target such as the spatial distance between different copies of the biomarker and the propensity of the probe/biomarker complex to self-aggregate.